Exploring the association between oral tactile sensitivity measures and phenotypic markers of oral responsiveness - Mani, Elisa; Ford, Rebecca; Pierguidi, Lapo; Spinelli, Sara; Ramsey, Imogen; Monteleone, Erminio; Dinnella, Caterina (Journal of texture studies, 2022)
This study investigated the individual variability in oral tactile sensitivity considering touch, by means of Von Frey Hair monofilaments (VFH) and spatial resolution, using the grating orientation test (GOT). The relationships of the two measures with 6‐n‐propylthiouracil (PROP) responsiveness and fungiform papillae density and size were investigated. One hundred and forty‐four subjects (48.6% women, aged 18–30) participated in the study. VFH and GOT thresholds were assessed by three‐down/one‐up staircase method. Responsiveness to 3.2 mM PROP was assessed on the general Labeled Magnitude Scale. Fungiform papillae density (FPD) and size were determined from automated counting. VFH thresholds appeared unsuitable to reveal individual variation in responsiveness to point‐pressure on the tongue. The frequency of GOT thresholds approximated a normal distribution and covered the whole range of variation, thus indicating an ability to measure individual variation in oral tactile sensitivity. No significant linear correlations were found between any of the oral tactile sensitivity measures and PROP responsiveness, FPD total and size class. VFH and GOT thresholds were not significantly associated. Agglomerative hierarchical clustering was used to classify participants for their PROP responsiveness, total FPD and GOT threshold. Three clusters were identified, C1 (n = 67), Cl2 (n = 42), and Cl3 (n = 35), differing for PROP responsiveness and FPD only. Results encourage future studies to explore association between GOT and both perception and preference for different food texture. Furthermore, deeper investigation of individual variability in sensitivity to different types of oral tactile stimuli would be helpful to capture differences in tactile sensitivity among the most sensitive individuals.